TEACHERS’ STRATEGIES IN TEACHING ENGLISH FOR YOUNG LEARNERS - Desi Surayatika (Universitas Indo Global Mandiri, 2022)
In this globalization era, people have to communicate globally. English plays a very important role especially in international communication. It is used in various activities like education, business, politics and technology. Consequently, it is taught in Indonesia to provide supplementary knowledge for communication. The importance of learning English cannot be ignored, it is the greatest common language spoken all over the world. In addition, learning English is very important to increase knowledge and language ability. In Indonesia, English has been introduced at kindergarten school, as the development of the world globalization that demand English skill for all people from different nation in the world. Every school has learned English, there is no need to fear but urgent need for wise adaptation and negotiation so that English becomes a powerful tool for gaining tremendous and unlimited knowledge for all kinds of subjects learned at school. Teaching English to young learners is not as easy as imagined, the teachers is not only help the students to get knowledge, competences and morality, but also have to prepare everything’s need. The teachers have to use many strategies in teaching such as applying various strategies, media and game in order to keep students’ interest in learning English. In this research, quantitative research was used that aim to find out teachers’ strategies in teaching English to young learners. The population was all of the teachers at one of kindergartens in Palembang, and the sample was selected through simple random sampling technique. In collecting the data, interview and questionnaire were used, and then the data was analyzed through descriptive method in this research. Based on the result of the research, it was found that there were three teaching and learning strategies used by the teachers in teaching English for young learners